Characteristics, management, and outcomes among admissions for primary cardiac tumors: Results from the National Inpatient Sample. Issue 10 (27th July 2021) - Heaton, Joseph N.; Dhaduk, Nehal; Okoh, Alexis K.; Dang‐Ho, Khoi P.; Tayal, Rajiv; Salemi, Arash; Waxman, Sergio
Abstract: Introduction: Primary cardiac tumors (PCT) are rare, and their contemporary outcomes are not well characterized in the literature. We assessed temporal trends in patient characteristics and management of admissions for PCT in US hospitals. Methods: Admissions with the principal diagnoses of a PCT (benign neoplasm of heart: ICD‐9 212.7, ICD‐10 D15.1; malignant neoplasm of heart: ICD‐9 164.1, ICD‐10 C38.0) between 2006 and 2017 were extracted from the National Inpatient Sample. Trends in demographics and clinical profiles were evaluated. We conducted descriptive analyses on the cohort and compared outcomes between those managed medically and surgically. Results: Between 2006 and 2017, 19, 111 admissions had the primary diagnosis of a PCT. Of these, 91.1% were benign. Admissions were mostly female (65.0%), caucasian (72.0%), and aged more than 50 years (76.0%). The annual admission rate for PCT was similar from 2006 to 2017 ( p trend > .05) and associated with congestive heart failure, diabetes, renal failure, and valvular lesions. PCTs were managed surgically in 12, 811 (67.0%) of overall cases, 70.8% for benign and 28.3% for malignant tumors. Overall, the in‐hospital mortality rate was 2.3%. Medically managed cases reported a 2.5% higher mortality ( p < .001) than those surgically managed. Admissions with malignant tumors were more likely to expire during hospitalization than those with benign tumors (odds ratio, 9.75; 95% confidence interval 6.34–14.99; p < .001). Conclusion: Admissions for primary cardiac tumors were primarily women or in their fifth or sixth decade of life. Surgical intervention is more commonly practiced and is associated with better in‐hospital survival.